A history of water : Being an account of a murder, an epic and two visions of global history - Wilson-Lee, Edward, ....- (London : William Collins, 2022)
It is the 30th of January 1574 and the king's archivist lies dead - burned or strangled or drowned. The paper found in his hand could be from any corner of the Portuguese empire. But whatever it contains is probably a lie. From award-winning writer Edward Wilson-Lee, this is a thrilling and true historical detective story set in sixteenth-century Portugal.
Keywords: History